Ownership structure, managerial behavior and corporate value - Davies, J.R.; Hillier, David; McColgan, Patrick (Journal of Corporate Finance, 2005)
The nonlinear relationship between corporate value and managerial ownership is well documented. This has been attributed to the onset of managerial entrenchment, which results in a decrease of corporate value for increasing levels of managerial holdings. We propose a new structure for this relationship that accounts for the effect of conflicting managerial incentives, and external and internal disciplinary monitoring mechanisms. Using this specification as the basis for our analysis, we provide evidence that the managerial ownership–corporate value relationship is co-deterministic. This finding is at odds with recent work which reports that corporate value determines managerial ownership but not vice-versa.